2014
DOI: 10.5505/tjtes.2014.04741
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationship Between Severity of Injury, Return to Work, Impairment and Activity Participation in Hand and Forearm Injuries

Abstract: ÖZET AMAÇ: Önkol ve el yaralanmaları işle ilişkili özrün temel nedenidir. Bu çalışmada, el ve önkol yaralanmaları sonrası hastaların yaralanma ciddiyetleri ile işe geri dönüş süresi, aktivite ve katılım düzeyleri arasındaki ilişki incelendi. GEREÇ VE YÖNTEM:Çalışmaya yaş ortalamaları 31±11.13 yıl (18-63 yıl) olan el ve önkol yaralanmalı toplam 130 hasta alındı. Modifiye El ve Önkol Yaralanması Ciddiyet Skorlaması (MEYCS) ile yaralanma ciddiyeti belirlendi. Yaralanmadan sonra sekizinci haftada Jebsen El Fonksiy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
6
2
1
Order By: Relevance
“…In the current study, the high score of the Quick DASH 60 showed a high disability due to occupational upper extremity injuries. Cakir et al found a strong relationship between the severity of injury and time to return to work and DASH scores (20). Kadzeilski et al, in a study on 51 cases with finger injuries, found a mean DASH score of 12, which was inconsistent with the results of the current study (21).…”
Section: Discussioncontrasting
confidence: 80%
“…In the current study, the high score of the Quick DASH 60 showed a high disability due to occupational upper extremity injuries. Cakir et al found a strong relationship between the severity of injury and time to return to work and DASH scores (20). Kadzeilski et al, in a study on 51 cases with finger injuries, found a mean DASH score of 12, which was inconsistent with the results of the current study (21).…”
Section: Discussioncontrasting
confidence: 80%
“…A higher severity injury score was correlated strongly with higher functional impairment. [28,29] Conclusion Zone 2 injuries, high MHISS values, and smoking were predictors of reoperation after primary flexor tendon repair. However, zone 2 injuries and high MHISS values cannot be modified, and can only be used as predictive indicators for the initial selection of patients who should be followed-up closely and managed comprehensively.…”
Section: Discussionmentioning
confidence: 91%
“…MHISS, which indicates the initial anatomic injury severity, provides an objective and comprehensive assessment. [27] MHISS is useful for predicting the duration of lost working time, [28] functional recovery [29] and future health-related quality of life. [30] We demonstrated that it is also useful to predict reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the relationship between the severity of upper extremity traumas, functional disability, and RTW. [2,6,7] On the other hand, the psychological status of the patients may also be affected by the severity of THIs. To our knowledge, in the literature, there is no study investigating the relationship between the severity of the injury and psychological morbidity in THI with major nerve involvement.…”
Section: Introductionmentioning
confidence: 99%